2006
DOI: 10.1510/icvts.2006.136937
|View full text |Cite
|
Sign up to set email alerts
|

Role of saphenous vein wall in the pathogenesis of primary varicose veins

Abstract: The findings in our study supported the theory of primary weakness of the vein wall as a cause of varicosity. This weakness is due to intimal changes, disturbance in the connective tissue components and smooth muscle cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 17 publications
6
44
0
10
Order By: Relevance
“…Vein wall inflammation causes medial smooth muscle cell proliferation and excess production of fibrous matter, leading to hyperplasia, which in turn reduces the elastic compliance of the vein wall. 10,11) The vein wall hyperplasia shown in Fig. 4 was considered to have been caused by the effects of lymphostasis-induced inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Vein wall inflammation causes medial smooth muscle cell proliferation and excess production of fibrous matter, leading to hyperplasia, which in turn reduces the elastic compliance of the vein wall. 10,11) The vein wall hyperplasia shown in Fig. 4 was considered to have been caused by the effects of lymphostasis-induced inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17] It has been suggested that these changes are due to chronic inflammation in the vein tissue. 14,18-20 Although we showed the increased wall thickness according to the ad- vanced clinical stages, it may be better to use the ratio between the vein wall thickness and the diameter, because wall thickness varies significantly with the size of the vein.…”
Section: Discussionmentioning
confidence: 99%
“…These findings in an overall markedly dilated vessel were comparable to those seen in varicose veins in the general population (Figure 2). 15 …”
Section: Case Report and Histologymentioning
confidence: 99%
“…This could support a genetic cause rather than a mechanical cause because genetic factors are known to strongly contribute to varicose veins. 15 There is abundant evidence from animal studies that venous patterning is under genetic control. 37,[40][41][42][43] Thus, we think that the vascular malformations defining KTS are caused by abnormal venous pattern formation due to genetic defects that may or may not be present in a mosaic state.…”
Section: Etiologymentioning
confidence: 99%